The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/pr9101733
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Characteristics of Methane Hedging Combustion in a Heat Cycle Porous Media Burner

Abstract: With the rapid development of portable devices and micro-small sensors, the demand for small-scale power supplies and high-energy-density energy supply systems is increasing. Comparing with the current popular lithium batteries, micro-scale burners based on micro-thermal photoelectric systems have features of high power density and high energy density, the micro-scale burner is the most critical part of the micro-thermal photovoltaic system. In this paper, the combustor was designed as a heat cycle structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Combustion in porous media has been widely investigated and proven to be well-suited for lean combustion on a wide range of different fuels. In [6][7], the effect of a porous media arrangement was studied on a CH 4 /air combuster, and the experimental and simulation results indicated that the inner and outer layers had a positive impact on the combustion process. Many studies focused on the usage of liquid fuels, such as kerosene and ethanol [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Combustion in porous media has been widely investigated and proven to be well-suited for lean combustion on a wide range of different fuels. In [6][7], the effect of a porous media arrangement was studied on a CH 4 /air combuster, and the experimental and simulation results indicated that the inner and outer layers had a positive impact on the combustion process. Many studies focused on the usage of liquid fuels, such as kerosene and ethanol [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%